PENGARUH LATIHAN MEDICINE BALL TERHADAP KEKUATAN OTOT LENGAN DAN BAHU PADA ATLET PUTRA BULUTANGKIS CLUB PB BANK RIAU KEPRI PEKANBARU - Ahmad Sobirin; Zainur Zainur; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The problem in this study is that the strength of the jump smash athletes of Club PB Bank Riau badminton sons of Riau Islands Pekanbaru is still lacking, this can be seen from various trials and official matches and this is one of the factors causing the defeat. This type of research is a type of experimental research to see the effect of the form of training. The purpose of this study was to look at the effect of medicine ball exercise on the strength of the arm and shoulder muscles in the athletes of Club PB Bank Riau badminton sons of Riau Islands Pekanbaru. The population in this study was PB Club Riau Kepri Pekanbaru, amounting to 6 people. The sampling technique is by using total sampling, where the total population is sampled. Data collection techniques obtained from the pre-test and post test. The instrument in this study used an expanding dynamometer as a tool to measure arm and shoulder muscle strength. The analysis was carried out using the t-test. based on data analysis and discussion, it can be concluded that there is a significant effect of medicine ball exercise on arm and shoulder muscle strength on the badminton athletes of Club PB Bank Riau badminton club Kepri Pekanbaru proven by the results of tcount of 13.23 and t table of 1.943. Means Thitung> T table. At the level of ɑ = 0.05.Key Words: Exercise medicine ball, arm and shoulder muscle strength